Fracture strength of In-Ceram™ prostheses fabricated by double sintering and glass infiltration - (:unkn) unknown (Trans Tech Publications Ltd, 2004)
For the In-Ceram™ system, the core needs to be sintered on a special plaster model and fired two times, first for 6 hours and then 2 more hours. In the fabrication of single piece jacket crowns with VITA In-Ceram™ sprint system, this time is reduced to 40 minutes. In this study by using the VITA In-Ceram™ sprint system, the pontic and crowns were prepared separately and these were connected to each other by a second sintering and glass infiltration procedure in order to decrease the firing time. The effects of this procedure on the fracture strength of the bridge prosthesis were investigated by 4-point bending tests on standard samples representing the pontic and crowns of a bridge prosthesis. Three different sample groups were prepared for the 4-point bending tests : a control group consisting of monolithic samples, a second group comprising separate samples with a connect distance of 1.5 mm and a third one having a connect distance of 1 mm. Whereas the control group had better bending strength values,there were no statistically significant differences between the strength values of the specimens of the other two groups. Scanning Electron Microscopy investigations were carried out to examine the fracture surfaces of the bending specimens.
Keywords: Flexural strength; Glass infiltration; In-Ceram™ system; Second sintering